FINISHING TEKNIK BATIK P ADA KERAJINAN KA YU DI SANGGAR KARY A MANUNGGAL - Martono, Martono; Suardana, Wayan; Hendri, Zulfi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The  object  of this  voucher  program  can  publicity  be reganded  to de velop  or enlarge  batik technique  finishing  on wood  craft.  The more  spesific objects  ot this  program  are as follows:  (1) To develop  design  of batik  mo tives  on wood  craft,   (2) To develop  liquit  wax  application   using  electrical canting  (drawing  pen),  (3) To develop  color  composed   variation  using "in digosol  ang  naptol",  (4) To despose  the  wax  using  gazoline  stove,  and  (5) Finishing   wooden   batik  after  drawing   proces   ti  preserve   the  color  from fungy using  anti fungy  Profan,  using wood  stain  Mowilex,  and Impra mela mine.The methode  of research  is to give  idea of developing  design  form anbatik   motives.   To  make   design   form   and   new   motive   design   to  give variative  choices.   Drawing  proces  using  traditional   canting  and  electrical canting.  Coloring  using painting  technique  and immersing  for indigosol  and immersing   technique   for  "naptol"     Wax  disposing   use  fire  ang  gazoline stove. The last preserved  finishing  use wood  stain  Mowilex,  melamine,  and antifungy  Profan.The  result  of this voucher  program  is  1) To develop  new design;  twoor three dimentional  form. Two dimentional   form is used in some ornaments such as "gunungan  sekaten,  baku! jamu   (herb  vendor),  and mask.  Three  di mentionan   form   includes   elephan   model,   bird   model,   horse   model,   cat model, and bridal  model.  2) Motive  design  included  some other varions  mo tives  besides    batik  motive  alot of design  choises.  3) Drawing  proses  uses traditional  canting  and electrical  canting  ( drawing  pen) and electrical  cant ing, is more  smoth  and  flat because  of the  stable  haet  resolted  more  clean and healty. 4) Coloring  using paiting technique  and immersing  technique  for indigosol   with  composition    10 grams  indigosol   + 250  ml  water  +  1 tea spoon TRO for painting  technique  and  10 gram  indigosol  + 1 liter water + 1 tea spoon TRO  for immersing  rechnique.  Material  adapting  color with com position  5 grams  nitrit  + 4 liter water  + 50 ml HCL.  Naptol  color  material compose  of 50 grams  naptol  + 10 gram  costic  + 1 tea spoon  TRO.  Salt for color  generate  compose  of  100 grams  salt  + 3 liter  water  . Disposing  wax with composition   of  1,5 kg soda abu + 20 liter water  boiled  using  gazoline stove.  The  proces  of the  disposing  wax  using  gazoline  stove  is more  clean and  healthy.   The  last  plated  after  drawing/batik    in  order  to  preserve   the2324color using  wood  stain, melamine,  ang using antifungy  Profan  . Understand ing the qualities  and its estetic,  there are some meaningful   changes  if we see it before and after the research.Key words: batik technique finishing,   wood craft